Advances in 3D-Printed scaffolds for bone defect repair: material strategies and synergistic functional performance - Tang, Xijie; Xu, Haijia; Liu, Xiangzhong; Yang, Yi; Li, Zhanghua (Frontiers in Bioengineering and Biotechnology, 2025)
Large bone defects remain a major clinical challenge, as traditional grafts and implants often fail to provide both long-term stability and biological integration. Three-dimensional (3D) printing offers unique advantages in fabricating patient-specific scaffolds with controlled architectures, enabling precise modulation of mechanics, degradation, and biological function. Natural and synthetic polymers, ceramics, and their composites have been widely explored, while strategies such as nanofiller reinforcement, surface modification, and growth-factor delivery further enhance osteogenesis, angiogenesis, immunomodulation, and anti-infection performance. This review systematically summarizes recent progress in 3D-printed biomaterial scaffolds for bone defect repair, focusing on their mechanical properties, degradation behavior, bioactivity, infection resistance, and vascularization. Current advances highlight how multifunctional design and material–biological coupling can bridge the gap between laboratory research and translational applications. Future directions emphasize material innovation, hierarchical scaffold design, and clinical standardization to accelerate the safe and effective application of 3D-printed scaffolds in bone regeneration.